Al-Syi’ru al-I’tiraf li Abi Nuwwas fi Dhaui 'Ilm al-Ma’ani - Supriyadi, Moh.; Hasbullah, M.; Taufiqurrahman, Su'udi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
Poetry is rooted from the word شعر- يشعر- شعرا- شعورا which means knowing, feeling, being aware of, composing, or composing a poem. According to Jurji Zaidan, poetry means singing (al-ghina`), chanting (insyadz), or chanting (tartil). The origin of this word has disappeared from Arabic, but is still present in other languages, such as شور in Hebrew which means voice, singing, and singing songs. Among the sources of the word syi`r is شير (syir) which means qasidah or singing. And the results of this research are about